The Movement of Western Honey Bees (Apis mellifera L.) Among U.S. States and Territories: History, Benefits, Risks, and Mitigation Strategies - Marcelino, Jose; Braese, Charles; Christmon, Krisztina; Evans, Jay D.; Gilligan, Todd; Giray, Tugrul; Nearman, Anthony; Niño, Elina L.; Rose, Robyn; Sheppard, Walter S.; vanEngelsdorp, Dennis; Ellis, James D. (Frontiers in Ecology and Evolution, 2022)
Beekeeping is a cornerstone activity that has led to the human-mediated, global spread of western honey bees (Apis mellifera L.) outside their native range of Europe, western Asia, and Africa. The exportation/importation of honey bees (i.e., transfer of honey bees or germplasm between countries) is regulated at the national level in many countries. Honey bees were first imported into the U.S. in the early 1600’s. Today, honey bee movement (i.e., transport of honey bees among U.S. states and territories) is regulated within the U.S. at the state, territory, and federal levels. At the federal level, honey bees present in the U.S. (in any state or territory) can be moved among U.S. states and territories without federal restriction, with the exception of movement to Hawaii. In contrast, regulations at the state and territory levels vary substantially, ranging from no additional regulations beyond those stipulated at the federal level, to strict regulations for the introduction of live colonies, packaged bees, or queens. This variability can lead to inconsistencies in the application of regulations regarding the movement of honey bees among U.S. states and territories. In November 2020, we convened a technical working group (TWG), composed of academic and USDA personnel, to review and summarize the (1) history of honey bee importation into/movement within the U.S., (2) current regulations regarding honey bee movement and case studies on the application of those regulations, (3) benefits associated with moving honey bees within the U.S., (4) risks associated with moving honey bees within the U.S., and (5) risk mitigation strategies. This review will be helpful for developing standardized best practices for the safe movement of honey bees between the 48 contiguous U.S. states and other states/territories.